Research On The Effects Of Transformational Leadership On Nurse Performance And OCB - Agustin (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2025)
This study aims to examine the influence of transformational leadership on nurse performance, both directly and through Organizational Citizenship Behavior (OCB) as a mediating variable, as well as assess the role of work commitment as a moderation variable in the relationship between OCB and performance. The study used an explanatory quantitative approach and was carried out on nurses at Bahteramas Hospital, Kendari City with a total of 179 respondents. Data was collected through surveys using structured questionnaires, measured on a five-point Likert scale from strongly disagree to strongly agree. The instrument was prepared by adapting indicators from previous research and adjusted to the context of health services. Data analysis uses Structural Equation Modeling based on Partial Least Squares because it is able to test the relationship between constructs simultaneously, is flexible to data that does not have to be normally distributed, and is suitable for testing direct influences, mediation, and moderation. The test results showed that transformational leadership had a positive and significant effect on OCB and nurse performance. OCB also has a positive and significant effect on performance, and has been proven to mediate the influence of transformational leadership on nurse performance. In addition, work commitment has been proven to moderate the influence of OCB on performance, so that the impact of OCB becomes stronger when nurses' work commitment is high.